A Case Study on CSR (Corporate Social Responsibility) systems and Funding to the CSOs (Community Service Organizations: Social Enterprises) in India - Tatpuje, Dipak; Boyd, Alec; Shende, Satish (IIUM Journal of Case Studies in Management, 2025)
This is an exploratory case study on Indian Corporate Social Responsibility (CSR) systems for funding Community Service Organizations (CSOs), conducted through a systematic literature survey and primary data collected from thirty Indian rural CSO functionaries in Maharashtra, regarding their perception, understanding of the CSR system, and preparedness for its utilization. The researchers conducted a systematic literature survey to identify gaps in the system. Researchers find that the Indian context has global insights with local actions. Minor CSOs functionaries working in rural areas are unaware of the mandatory requirement for registration and the processes for accessing the CSR funds facility through the portal. Therefore, digital literacy and skilling need to be addressed through capacity building in Information and Communication Technology. There is a need for training to upskill CSOs. The revolution in Indian CSR processes, brought about by timely amendments to the Companies Act, has impacted and initiated a new era of social development.